Marketing strategies for the generation "C" consumer behavior: An overview for the GSM market in Turkey - (:unkn) unknown (IGI Global, 2014)
Generations are mainly listed as the silent generation, Generation X, Generation Y, Generation Z, and lastly, Generation C. Among them, "Generation C" is the new target market of the strategists with their high use of technology and changing consumer behavior. Especially with the conveniences provided by the Internet, while the world is getting smaller and more global, it is foreseen that this generation, who tend to live mobile and who are active media users, will change the equilibrium in the future. In this chapter, generation C's consumer behavior and the marketing strategies developed for them are explored. As GSM sector is assumed to be one of the most important sectors of this generation, a good member of Turkish GSM market, Turkcell's, approach to this generation is surveyed in the frame of this new generation. © 2015 by IGI Global. All rights reserved.